2020
DOI: 10.1002/ajmg.a.61582
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of malformation associated with esophageal atresia/tracheoesophageal fistula: A retrospective single center study

Abstract: Esophageal atresia/tracheoesophageal fistula (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 60 publications
(94 reference statements)
5
10
0
1
Order By: Relevance
“…The incidence of anomalies associated with EA ± TEF ranges between 30% and 60% in different studies. [ 5 10 11 ] In ours, 50% had VACTERL association similar to Galarreta et al study. [ 11 ] Half of the cases with DA were associated with Down syndrome as reported in previous studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The incidence of anomalies associated with EA ± TEF ranges between 30% and 60% in different studies. [ 5 10 11 ] In ours, 50% had VACTERL association similar to Galarreta et al study. [ 11 ] Half of the cases with DA were associated with Down syndrome as reported in previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…[ 5 10 11 ] In ours, 50% had VACTERL association similar to Galarreta et al study. [ 11 ] Half of the cases with DA were associated with Down syndrome as reported in previous studies. [ 6 ] Genetic predisposition along with environmental factors have been implicated in the pathogenesis of IHPS.…”
Section: Discussionsupporting
confidence: 89%
“…Most of the study do not represent any gender differences, but in our study the number of male patients were more compared to the female counterpart. Such findings have also been identified in some studies [15,17,[22][23][24] . This could be attributed to preference to male child in our country and increasing feticide leading to hospital admission bias.…”
Section: Discussionsupporting
confidence: 83%
“…At present, it is difficult to make prenatal diagnosis of EA. It was reported that only about 1/3 of EA cases were diagnosed before delivery [ 12 ]. In recent years, magnetic resonance imaging (MRI) has been used in the prenatal diagnosis of EA.…”
Section: Discussionmentioning
confidence: 99%